A história de Mestre Tomáz e a poesia do Carimbó em São João de Pirabas - TAVARES, Luana da Fonseca (2025)
This project aims to understand the importance of poetry in the form of carimbó, by Mestre Tomáz (1939-2018), for the municipality of São João de Pirabas. It seeks to understand the way in which Mestre Tomáz emerges as a reference of popular culture in Pirabas, considering that he is one of the masters of the culture inventoried by the National Historical and Artistic Heritage Institute (IPHAN). The research aims to verify how the population of Pirabas recognizes the legacy left by the master, whether they perceive his compositions as telling the story of their people and their culture. In this context, the concepts to be worked on are local history, memory and popular culture. The methodology adopted will consist of field research, with interviews, seeking to find the presence of Mestre Tomáz in the narratives about the local history and culture of Pirabas. During the investigation, personal documents from family members will also be analyzed, such as photographs and writings, as well as materials related to the practice of the dance, including drums, handmade flute, ganzá, reco-reco, banjo, maracás, afoxé, tambourines and the group's clothing. The aim is to understand how Mestre Tomáz is inserted into the local history of Pirabas. The hypothesis is that Mestre Tomáz plays an important role in the historical development of the municipality through his carimbó, although it is not widely recognized by the population.